Brood Reduction by Infanticide in Peregrine Falcons - Franke, Alastair; Galipeau, Philippe; Nikolaiczuk, Laurent (ARCTIC, 2013)
This note describes an observation of infanticide in the Peregrine Falcon (Falco peregrinus tundrius). During the summer of 2011, a marked adult female and an unmarked adult male produced and hatched two eggs at a known and regularly monitored nest site. Motion-sensitive camera images indicated that the adults attended to the two nestlings and fed them in a manner that resulted in growth and development typical for the nestlings produced in the study population. During a period of intense rainfall, the two nestlings were left unattended for several hours; both nestlings were clearly distressed, and one was close to death. When the visibly wet marked adult female returned to the nest ledge, she killed and partially consumed the smaller and weaker of the two nestlings. The female flew from the nest ledge without feeding the remaining nestling and returned shortly afterward to kill and partially consume the second nestling. This is the first documentation of infanticide in wild Peregrine Falcons. Cet article décrit une observation d’infanticide chez le faucon pèlerin (Falco peregrinus tundrius). À l’été 2011, une femelle adulte baguée et un mâle adulte non bagué ont produit et couvé deux oeufs à un site de nidification connu qui fait l’objet d’une surveillance régulière. Les images de caméras à détection de mouvement ont permis de constater que les deux adultes se sont occupés des deux oisillons et les ont nourris au point où ils ont pu grossir et se développer de manière typique aux autres oisillons visés par la population à l’étude. Pendant une période de pluie intense, les deux oisillons ont été laissés à eux-mêmes pendant plusieurs heures. De toute évidence, les deux oisillons étaient en détresse, et l’un d’entre eux se mourait. Lorsque la femelle adulte baguée visiblement trempée a regagné la corniche, elle a tué et consommé partiellement l’oisillon le plus petit et le plus faible. Ensuite, la femelle s’est envolée de la corniche sans nourrir l’autre oisillon, puis elle est revenue peu après pour tuer et ...